The Association of Dietary Insulin Index and Load with Resting Metabolic Rate (RMR) in Women Referred to Health Centers of Tehran University of Medical Sciences - Hossein Hassani; Maryam Arab-Moorchegani; Narges Parsaie; Mahshid Rezaei; Khadijeh Mirzaei; Hossein Imani; Mir Saeed Yekaninejad (Tehran University of Medical Sciences, 2022)
Background and Aim: Currently, utilizing different nutritional indicators to investigate the association between diet and various diseases is considered in previous studies, which is related with some chronic diseases. However, no studies have studied the connection between the indicators with the rate of metabolism at rest (RMR). Therefore, the present study aimed to determine the relationship between dietary index and insulin load with resting metabolic rate (RMR) in overweight and obese women Materials and Methods: A total of 280 healthy overweight and obese women (aged 18-50 years) who were referred to community health centers of Tehran University of medical sciences were included. In this study anthropometrics measurements such as weight, height, waist circumference, waist to hip ratio, body mass index, fat percentage, and fat-free mass were evaluated for every participant. Data on dietary intakes were collected using 147 semi-quantitative food frequency questionnaire (FFQ). DII and DIL were calculated using food insulin index values published earlier. To assess the RMR, indirect calorimetry was used.  Results: Mean age of study participants was 36.4±8.38 years. Although a significant association was seen between DII and RMR in a crude model (P=0.04); adjusting for different confounders made this significant relationship between DII and RMR insignificant. In addition, the dietary insulin index had no significant relationship with the amount of RMR/kg (p=0.63) and RMR/FFM (p=0.73). Conclusions: Based on the results of this cross-sectional study, it seems that the insulin index and insulin load of the diet are not associated to the rate of resting metabolism. However, due to the limitations of this study, findings can only confirm or reject the hypothesis under further studies. It is also necessary to determine the role of dietary insulin indicators on human health, especially with a Study Prospective Design